Energy Utilization and Performance of Madura Cattle Fed with Two Kinds of Rice Straw Processing and Concentrate Supplemented Teak Leaf Flour (Tectona grandiss) - Kasihandari, Yut Afiffah; Bata, Muhamad; rahayu, Sri; Rimbawanto, Efka Aris; Prayitno, Caribu Hadi (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
This study aims to investigate the effect of the interaction between the type of rice straw processing and the concentration of teak leaf flour supplementation on energy intake and performance of Madura cattle. A total of 18 Madura cattle with an average weight of 246.5 ± 10.29 kg were placed in individual pens and randomly assigned to either ammoniated or non-ammoniated rice straw processing and concentrate with different supplementations of teak leaf flour (TLF): 0% (T1), 0.21% (T2), and 0.42% (T3) of dry matter. This study used a completely randomized design with a 2 x 3 factorial and Tukey's range test or orthogonal polynomials. The observed variables were dry matter intake (DMI), energy intake (EI), digested energy (DE), retained energy (RE), RE:EI efficiency, RE:DE efficiency, average daily gain (ADG), feed conversion (FC), and slaughter weight. The results showed no interaction between the type of rice straw and the concentration of TLF on all variables (p > 0.05). The type of rice straw processing did not significantly affect all variables (p > 0.05). TLF supplementation had a quadratic effect on EI, DMI, and slaughter weight. Madura cattle fattening fed with either ammoniated or non-ammoniated rice straw combined with concentrate supplemented with TLF resulted in an increase in feed intake and final body weight.